Effects of Fat Source and Level on Growth Performance, Carcass Characteristics, Carcass Iodine Value and Economics of Finishing Pigs in a Commercial Environment - Jenna J. Bromm; Joel M. DeRouchey; Mike D. Tokach; Kiah M. Berg; Jon A. De Jong; Courtney L. Pohlen; Jason C. Woodworth; Robert D. Goodband; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2022)
A total of 2,011 pigs (PIC 1050 × DNA 600; initially 62.4 ± 4.6 lb) were used in a 113-d finishing trial to evaluate the effects of two different fat sources fed at two different levels on growth performance, carcass characteristics, carcass iodine value, and economics of finishing pigs raised in a commercial environment. Pigs were randomly allotted to 1 of 5 dietary treatments with 21 to 27 pigs per pen and 16 pens per treatment. Dietary treatments were arranged in a 2 × 2 + 1 factorial with main effects of fat source and fat inclusion level. Dietary treatments included a control diet containing no added fat. The other 4 dietary treatments included two different fat sources, choice white grease or corn oil, included at either 1 or 3% of the diet. Experimental diets were fed based on a feed budget from d 0 to 113 in 6 phases. For overall growth performance, pigs fed increasing dietary fat from 0 to 3% had increased (linear,P<0.001) ADG and decreased (linear,P= 0.013) ADFI, which led to an improvement (linear,P<0.001) in F/G. There was no difference in growth performance between pigs fed choice white grease or corn oil. For carcass characteristics, increasing fat increased (linear,P≤ 0.017) HCW, carcass yield, and backfat. For carcass fat iodine value, there was a fat source × level interaction (P<0.001) where iodine value increased linearly as corn oil increased in the diet with only a small increase in iodine value when diets with choice white grease were fed. For economics, increasing fat, regardless of fat source, increased feed cost (linear,P<0.001) and revenue (linear,P= 0.003). Increasing fat reduced (linear,P<0.001) IOFC in the high feed cost, low revenue scenario, and tended to increase (P= 0.060) IOFC in the low feed cost, high revenue scenario. In conclusion, increasing fat from 0 to 3% of the diet, regardless of fat source, increased overall ADG, reduced ADFI, and improved F/G. Increasing fat also increased HCW, carcass yield, and backfat, while pigs fed diets containing corn oil had higher carcass fat iodine values. When feed costs are high and revenue is low, the improvement in growth performance does not justify the extra diet cost from increasing added fat from 0 to 3% in the diet. However, adding fat in the diet is justifiable when feed costs are low and revenue is high, regardless of fat source used.
Keywords: carcass characteristics; fat level; fat source; growth performance; iodine value